Stressors, Organization Citizenship Behavior and Islamic Work Ethics - MUHAMMAD TUFAIL; ANUM; SAQIB SHAHZAD; DR. JEHANGIR (Journal of Business & Tourism, 2021)
In response to the need of study fulfilling the interplay between stressors and job outcomes, the present study has been carried out. We also examined the moderating role of Islamic Work ethics in the proposed relationship. Based on the purposive sampling technique, a sample of 287 employees working in Public sector organizations were selected. Results of the study supported the proposed hypotheses, indicating that the challenge stressors have positive and hindrance stressors have negative relation with organizational citizenship behavior. We also found that the Islamic Work Ethics moderates the said relationship in such a way that higher level of Islamic Work Ethics strengthen the relationship between challenge stressors and organization citizenship behavior and weaken the relationship between hindrance stressors and organization citizenship behavior.